2007
DOI: 10.1063/1.2711419
|View full text |Cite|
|
Sign up to set email alerts
|

Tuning optical band gap of vertically aligned ZnO nanowire arrays grown by homoepitaxial electrodeposition

Abstract: Vertically aligned ZnO nanowire arrays are grown homoepitaxially on the ZnO seeded indium tin oxide substrate by electrochemical deposition from aqueous solution at low temperature (70°C) without using any template. ZnO nanowires exhibit single crystalline, wurtzite crystal structure determined by transmission electron microscopy and powder x-ray diffraction. The ZnO nanowire arrays show high transmittance in the visible wavelengths. Interestingly, the optical band gap of the ZnO nanowire arrays has been tuned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 25 publications
3
42
0
Order By: Relevance
“…The ZnO nanowire arrays showed high transmittance Nano Res 9 in the visible range due to the large electronic band gap. Interestingly, the band gap of the ZnO nanowire arrays could be tuned by simply changing the zinc precursor concentration during the electrodeposition [127].…”
Section: Electrodepositionmentioning
confidence: 99%
“…The ZnO nanowire arrays showed high transmittance Nano Res 9 in the visible range due to the large electronic band gap. Interestingly, the band gap of the ZnO nanowire arrays could be tuned by simply changing the zinc precursor concentration during the electrodeposition [127].…”
Section: Electrodepositionmentioning
confidence: 99%
“…[10][11][12][13] The ED of ZnO nanowires has been focused mostly on the preparation of nanorod/nanowire arrays by the template method and on flat substrates. 14,15 The ZnO electrodeposition is based on the reduction of an oxygen precursor such as dissolved molecular oxygen, nitrate ions or hydrogen peroxide. For example, Cembrero et al 16 reported on the cathodic electrodeposition of ZnO nanocolumns and nanowires from zinc chloride solutions saturated in molecular oxygen.…”
mentioning
confidence: 99%
“…These techniques for the growth of doped and undoped ZnO nanorods include metal-organic chemical vapour deposition (MOC-VD), metal-organic vapour phase epitaxy (VPE), pulsed laser deposition (PLD), Carbo-thermal evaporation (CTE), aqueous chemical growth (ACG) electro deposition (ED) and hydrothermal deposition (HD) (Wu and Liu, 2002;Bakin et al, 2007;Nobis et al, 2004;Czekalla et al, 2008;Vayssieres et al, 2001;Illy et al, 2005;Park et al, 2002;Anthony et al, 2007;Damen et al, 1966). The route of synthesis reported in this paper is wet and solution based.…”
Section: Introductionmentioning
confidence: 98%